Enhancing ICT Literacy and Achievement: A TPACK-Based Blended Learning Model for Thai Business Administration Students - Cherisa Nantha; Kobchai Siripongdee; Surapong Siripongdee; Paitoon Pimdee; Thiyaporn Kantathanawat; Kanitphan Boonsomchuae (My University, 2024)
The COVID-19 pandemic has heightened the need for 21st century skills, particularly computer and ICT literacy (CICT) in Thailand. This study aimed to develop a TPACK (Technological Pedagogical and Content Knowledge)-based blended learning model (BLM) to enhance CICT skills and academic performance among 179 Business Administration (BA) undergraduates in the 2022 academic year Computer and Information Applications course. Research instruments were designed and evaluated by experts. Over 18 weeks, qualitative and quantitative data were collected, with the qualitative data undergoing content analysis. Descriptive statistics were used to analyze quantitative data, comparing pretests, post-tests, and 2-week retests using a repeated measure ANOVA. One-sample t-tests were used to assess the model’s impact on CICT skills. The results showed a significant score improvement between tests, with the highest mean being seen in the 2-week retest. The BA-TPACK model significantly enhanced CICT skills, exceeding 80%. The students expressed high satisfaction, with the BA-TPACK model effectively enhancing CICT skills and academic achievement, recommending its integration into future computer and information courses. This study’s contribution lies in addressing the pressing need for CICT skills in the ‘new normal’. By developing and implementing a BLM grounded in the TPACK framework, this study not only enhances students’ CICT proficiency but also fills a crucial gap in the literature regarding effective pedagogical approaches to foster 21st century skills.
Keywords: Blended Learning; Online and Blended Learning